A Study on the Possible Link of Brucellosis to Increased Stillbirths in the Maltese Islands from 1919 to 1954 - Lianne Tripp; Larry A. Sawchuk; Mahinda Samarakoon (Wiley, 2024)
ABSTRACT Background Human brucellosis, otherwise known as undulant fever, is one of the most widespread zoonotic diseases in the world. Even though 9%-15% of stillbirths are known to be caused by infectious diseases, the study of the link between human Brucella melitensis and the termination of births in humans is a topic that has received little attention. This study examines if there was an association between infection of undulant fever, an endemic zoonotic disease in the Maltese Islands from 1919 until 1954, and reproductive loss through stillbirths. Methods A univariate descriptive analysis was used to show the temporal trend of undulant fever time, as well as the age and sex distribution. Time series analysis was used to assess the relationship between time (months) and undulant fever cases with stillbirth proportions. Results On the island of Gozo, the majority of undulant fever cases for both males and females occurred in their reproductive period between 15 and 45 years of age. Based on regression analysis, undulant fever had a statistically significant effect on the stillbirth rate for males (t = 2.8986, p = 0.0039). The effect of undulant fever on stillbirths was not significant for females (p = 0.9103). Conclusion This paper highlights the importance of undulant fever as having implications for the health burden in pregnant women and potential fetal loss through stillbirths in the contemporary context.